Graphite nanoparticle addition to fertilizers reduces nitrate leaching in growth of lettuce (Lactuca sativa). Issue 1 (1st November 2019) - Pandorf, Madelyn; Pourzahedi, Leila; Gilbertson, Leanne; Lowry, Gregory V.; Herckes, Pierre; Westerhoff, Paul
Abstract : This study focused on nitrate leaching through soil during growth of romaine lettuce where 2-D graphite (CNPs) were combined with fertilizer and applied to soil to test the CNP effect on yield, nitrate leaching, and plant nutrient uptake. Abstract : Nitrogen leaching into groundwater occurs in nearly all intensively-fertilized agriculture applications and poses growing environmental and human health risks such as eutrophication and drinking water contamination. This potential for contamination will intensify as the population grows. This study focused on nitrate leaching through soil during the growth of romaine lettuce ( Lactuca sativa ), a high value crop in a region (Salinas Valley, CA) suffering from nitrate-contaminated water. 2-D graphite carbon nanoparticles (CNPs) produced via an electrochemical exfoliation process, resulting in ∼8 nm thickness and 250–850 nm width, were combined with fertilizer and applied to the lettuce in soil to test the CNP effect on yield, nitrate leaching, and plant nutrient uptake. Greenhouse experiments were conducted under different nutrient loadings and soil matrices. CNP addition did not inhibit the lettuce leaf yield, and decreased nitrate leaching in several scenarios. When fertilizer was reduced to 70% of the recommended dose and combined with less than 1% wt CNPs, nitrate leaching decreased by 57%. Furthermore, there was no significant difference in yield compared to the 100% recommended fertilizer dose without CNPs. Increasing the soil's hydraulic conductivity enhanced the ability of CNPs to reduce nitrate leaching and increase plant nitrogen uptake. CNP addition to mineral fertilizer blends may allow lower fertilizer doses and thus decrease nitrate infiltration through the soil without comprising yields.